The influence of salt reduction with encapsulated oleoresins on the quality of mayonnaise, mustard, and ketchup - Serrano, Carmo; Sapata, Margarida; Castelo-Branco, Diogo; Tasso, Ana; Marques, António; Viegas, Cláudia; Figueira, Diogo; Komora, Norton (Frontiers in Nutrition, 2024)
Introduction: Mayonnaise, mustard, and ketchup are table sauces enjoyed worldwide, adding flavour and texture to many dishes. However, these products often contain high sodium content, which contributes to health issues such as high blood pressure and cardiovascular disease. To address these concerns, reducing salt content in the sauces has become a significant goal for both manufacturers and consumers. Objectives: This study investigates the effects of three formulations of microencapsulated (ME) oleoresins (F1, F2, and F3), derived from aromatic plants and spices, on the mineral content, physical-chemical properties, colour, and sensory profiles of mayonnaise, mustard, and ketchup. Results: The addition of ME ingredients led to substantial salt reductions in all sauces—up to 50% in mayonnaise, 45% in mustard, and 52% in ketchup—meeting EU sodium guidelines and enabling a "reduced Na/NaCl content" nutrition claim. Potassium levels in mustard and ketchup supported health claims for blood pressure maintenance, while chloride content was reduced, aligning better with dietary reference values. Physical-chemical analysis showed minimal impact from ME ingredients on parameters like pH, lipid oxidation, and viscosity, with notable differences in ketchup consistency and chloride content in mustard and ketchup. Inulin, used as a carrier agent, helped preserve the sauces' rheological properties, with mustard showing the most similarity to the control. Colour analysis revealed minimal changes in mayonnaise, moderate changes in mustard, and significant differences in ketchup, particularly with the ME-F3 formulation, where the light-yellow ME ingredients notably affected the darker sauce. Despite these variations, sensory analysis indicated that the ME formulations had overall sensory profiles similar to the control in all sauces. Mayonnaise showed the closest resemblance, mustard had slightly lower flavor and saltiness scores, and ketchup exhibited no significant sensory differences compared to the control. Conclusions: These findings indicate that ME ingredients can be successfully utilized in condiment reformulation to achieve significant salt reduction without compromising taste. Incorporating ME-based strategies and low-sodium alternatives allows consumers to enjoy their favorite sauces while reducing sodium intake. This approach supports health-related claims and aligns with the industry's commitment to providing more nutritious options.